Technologically Influential Hospitality: Recognizing the Drivers of Smart Hotel Visitation - Arif Zulkarnain; Tiurida Lily Anita; Tri Wiyana; Abdul Rauf Ridzuan (Universitas Mercu Buana, 2025)
Objectives: Following the concept of smart hotels, this study aims to analyze the relationship between technology readiness, amenities, perceived usefulness (PU), perceived ease of use (PEOU), and visiting intentions. In addition, this study seeks to identify specific elements of technology amenities that significantly influence guests' intention to visit. Thus, this study is expected to fill a gap in the literature and propose a more comprehensive conceptual framework for understanding guest behavior in the context of smart hotels.Methodology: This study used quantitative research methods with the unit of analysis being visitors to five-star hotels in Jakarta. Purposive sampling was used to select participants who met the research criteria, resulting in a total of 290 respondents. Data collection was conducted using an online questionnaire distributed through social media. Data analysis techniques used in this study included Partial Least Squares - Structural Equation Modeling (PLS-SEM) to test the relationship between variables.Finding: The results indicate that technology amenities significantly affect PEOU, PU, and visiting intention. Meanwhile, technology readiness affects PEOU and PU but does not directly influence visiting intention. PU and PEOU mediate the influence of TR and TA on visiting intention, indicating that perceptions of ease and usefulness are the main mechanisms that bridge the relationship between technological factors and consumer behavior.Conclusion: This study concludes that technology amenities have a significant effect on PEOU, PU, and visit intention. Meanwhile, technologyl readiness affects PEOU and PU but does not directly affect visit intention. PU and PEOU become mediating variables of the effect of TR and TA on visit intention.